Science and Scholars during the time of the Buyid dynasty in Iraq - العلو, فراس (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The lands of Islam were united under the Abbasid Caliphate, but after they became weak, they were divided in to small states ruled by princes and sultans, each of whom ruled his state away from the authority of the Abbasid caliph, who only had Baghdad in his hands, the capital of the state, which contributed to the Buyids taking control of power in the year 334 AH in Baghdad, They preserved the Abbasid caliphs, but without political authority, as they were the ones who commanded and prohibited, The scientific movement was greatly active during the reign of the Buraymites, as they attracted great scholars from various fields, showered them with gifts, and contributed to the establishment of schools, mosques, and libraries. They also encouraged students of knowledge and provided them with placesto study and food, the Buyid palaces were ablaze with scientific debates until the Buyid rulers themselves became active in the sciences and took an interest in them, as well as the princes of the Buyids and their ministers, who competed to seek knowledge, encourage sciences and scholars, and provide what they needed for the sake of knowledge, the shops of al- waraqin also contributed to the scientific renaissance in the Buraimi era and the translation movement from other languages and different types of knowledge, until Baghdad became a destination for scholars and students of knowledge from all parts of the world, and during the Buraimi era, scientific books began to be translated in to various languages in pursuit of knowledge and knowledge.